Closing, opening and reopening: the difficult coexistence - Ferluga, Massimo; Lucangelo, Umberto (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Volume-controlled ventilation (VCV) has always been considered as protective ventilation, in particular during spontaneous breathing, being able to avoid the administration of injurious tidal volumes (Vt) to the patient. In fact, spontaneous efforts increase transpulmonary pressure (Pl) only during pressure-regulated ventilations (1). Despite this difference in terms of Pl, the conditions of lung parenchyma determine the damage to the lung tissue and the onset of ventilator induced lung injury (VILI).